5x-4=-2+3x

Simple and best practice solution for 5x-4=-2+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-4=-2+3x equation:


Simplifying
5x + -4 = -2 + 3x

Reorder the terms:
-4 + 5x = -2 + 3x

Solving
-4 + 5x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-4 + 5x + -3x = -2 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-4 + 2x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-4 + 2x = -2 + 0
-4 + 2x = -2

Add '4' to each side of the equation.
-4 + 4 + 2x = -2 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = -2 + 4
2x = -2 + 4

Combine like terms: -2 + 4 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| 158-2x=34x+22 | | x^2-14x+29=-3x+5 | | 8m^2-16m+8=0 | | 12-7x=177-42x | | x^2-18x+40=-5x | | 3x+36=5x*12 | | 7a+3=2a+8 | | 7x-6=70 | | x-x/10=189 | | 3y^3+2y^2-9y-6= | | k-3.5=21 | | 4x+3x-7=0 | | 71-12.50=c | | -62-7x=177-42x | | 4x^3-256= | | 5x+12=-2(6x+11) | | 3(x+3)=27 | | x-19=-33 | | x+29=4 | | 9+9=90 | | x+22=11 | | m^2+m-30=0 | | 3x+40=6x+14 | | 10x-9=-8x+3 | | y-6=-12(x+4) | | (x+4)/5=10 | | x-9=-27 | | 4+4=20 | | 4h+-13=7h+3 | | x-14=-21 | | 4x-9=2x+15 | | x+25=2 |

Equations solver categories